Principles of Aeroelasticity - Bisplinghoff, Raymond L; Ashley, Holt (Dover Publications, Incorporated, 2013)
Geared toward professional engineers, this volume will be helpful for students, too. Topics include methods of constructing static and dynamic equations, heated elastic solids, forms of aerodynamic operators, structural operators, and more. 1962 edition.